Integration of Risk Management into Management Control System from a Pragmatic Constructivist Perspective - Janiak, Magdalena (Proceedings of Pragmatic Constructivism, 2017)
The idea of the paper is to inform risk management (RM) with the pragmatic constructivist (PC) perspective, and to simultaneously integrate risk management with management control systems (MCS) bearing in mind that the key to the PC perspective is that risk information has both subjective and objective components. The paper will (1) Show how to improve Risk Management systems using the Pragmatic Constructivist perspective. (2) Demonstrate how to use the Pragmatic Constructivist perspective to integrate Risk Management into Management Control Systems. (3) Provide a case study to apply the theory by showing how Management Control System can govern Risk Management from Pragmatic Constructivist perspective. Applying the case study finds out mainly that action control in a form of two-way communication between actors (managers and technicians) at the process of risk identification, risk analysis, decision making and monitoring, risk reality is necessary. Results controls direct attention to facts entered by actors according to their expertise and level of influence. Personnel control enables to choose people with common values and necessary competencies to share knowledge for risk management. In this way actor-based reality with the actors being co-authors of the reality can take place. The main implications of the research suggest that: 1) the successful integration of RM into MCS requires pragmatic constructivist reality to applied by providing the contribution from all the actors so that the RM system is practical, and 2) RM should be designed to gather some subjective data from the ground level (e.g. on the probability of an incident recurring and the potential costs of any particular type of incident) to balance the objective information gathered so that the PC approach can support RM and MCS.